The Influence Of Content Marketing, Online Customer Reviews, And Product Quality On Interest In Buying Mykonos Perfume Products On Shopee E-Commerce (Study On Generation Z In Surabaya) - Marcella Arthamevia Arifin; Siti Ning Farida (UNIVERSITAS PAKUAN, 2026)
This study aims to identify and analyze the influence of Content Marketing, Online Customer Reviews, and Product Quality on Generation Z’s purchase intent for Mykonos perfume products on the Shopee e-commerce platform in Surabaya. The research method employed is a quantitative method using an associative approach. Data collection was conducted by distributing questionnaires to respondents. The sample in this study consisted of 157 Generation Z respondents in Surabaya who were aware of or had seen Mykonos perfume products on Shopee. The data analysis techniques used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination using SPSS software. The results of the study indicate that Content Marketing, Online Customer Reviews, and Product Quality simultaneously have a significant effect on the purchase intention for Mykonos perfume products. Partially, Content Marketing has a positive and significant effect on purchase intention, Online Customer Reviews have a positive and significant effect on purchase intention, and Product Quality has a positive and significant effect on the purchase intention for Mykonos perfume products on the Shopee e-commerce platform. These findings indicate that the better the content marketing strategy, the more positive the customer reviews, and the higher the product quality, the greater consumers’ interest in purchasing Mykonos perfumes will be.